Functional, Antigen-Specific Stem Cell Memory (TSCM) CD4+ T Cells Are Induced by Human Mycobacterium tuberculosis Infection - Mpande, Cheleka A. M.; Dintwe, One B.; Musvosvi, Munyaradzi; Mabwe, Simbarashe; Bilek, Nicole; Hatherill, Mark; Nemes, Elisa; Scriba, Thomas J.; , The SATVI Clinical Immunology Team; Ontong, Cynthia; Filander, Elizabeth; Alexander, Fadia; et al. (Frontiers in Immunology, 2018)
BACKGROUND: Maintenance of long lasting immunity is thought to depend on stem cell memory T cells (TSCM), which have superior self-renewing capacity, longevity and proliferative potential compared with central memory (TCM) or effector (TEFF) T cells. Our knowledge of TSCM derives primarily from studies of virus-specific CD8+ TSCM. We aimed to determine if infection with Mycobacterium tuberculosis (M.tb), the etiological agent of tuberculosis, generates antigen-specific CD4+ TSCM and to characterise their functional ontology. METHODS: We studied T cell responses to natural M.tb infection in a longitudinal adolescent cohort of recent QuantiFERON-TB Gold (QFT) converters and three cross-sectional QFT+ adult cohorts; and to Bacillus Calmette-Guerin (BCG) vaccination in infants. M.tb and/or BCG-specific CD4 T cells were detected by flow cytometry using MHC-class II tetramers bearing Ag85, CFP-10 or ESAT-6 peptides, or by intracellular cytokine staining. Transcriptomic analyses of M.tb-specific tetramer+ CD4+ TSCM (CD45RA+CCR7+CD27+) were performed by microfluidic qRT-PCR and functional and phenotypic characteristics were confirmed by measuring expression of chemokine receptors, cytotoxic molecules and cytokines using flow cytometry. RESULTS: M.tb-specific TSCM were not detected in QFT-negative persons. After QFT conversion frequencies of TSCM increased to measurable levels and remained detectable thereafter, suggesting that primary M.tb infection induces TSCM cells. Gene expression profiling of tetramer+ TSCM showed that these cells were distinct from bulk CD4+ naïve T cells (TN) and shared features of bulk TSCM and M.tb-specific tetramer+ TCM and TEFF cells. These TSCM were predominantly CD95+ and CXCR3+, markers typical of CD8+ TSCM. Tetramer+ TSCM expressed significantly higher protein levels of CCR5, CCR6, CXCR3, Granzyme A, Granzyme K and Granulysin than bulk TN and TSCM cells. M.tb-specific TSCM were also functional, producing IL-2, IFN-γ and TNF-α upon antigen stimulation, and their frequencies correlated positively with long-term BCG-specific CD4+ T cell proliferative potential after infant vaccination. CONCLUSIONS: Human infection with M.tb induced distinct, antigen-specific CD4+ TSCM cells endowed with effector functions, including expression of cytotoxic molecules and Th1 cytokines, and displayed chemokine receptor profiles consistent with memory Th1/17 cells. Induction of CD4+ TSCM should be considered for vaccination approaches that aim to generate long-lived memory T cells against M.tb.